EPR study of the relationship between ultra high molecular weight polyethylene structure and radicals formed during irradiation with high energy sources. (5th November 2014) - Brunella, Valentina; Paganini, Maria Cristina
<x xml:space="preserve">Abstract</x> Three different samples of ultra high molecular weight polyethylene have been irradiated with a high energy source (electron beam), and radicals have been generated. Different radical species have been assigned on the basis of their electron paramagnetic resonance spectra. Electron paramagnetic resonance data have been used also to evaluate the amount of each kind of radical that has been generated on different starting materials. The structure of the polymer (number of double bonds or crystallinity) is strictly connected to the response of the sample itself to the irradiation. A rationalization between these different parameters has been performed in order to evaluate the stability of polymer samples toward high energy irradiation processes. Copyright © 2014 John Wiley & Sons, Ltd.